Analysis of Crayfish Catches Using Bubu Wau in Laut Tawar Lake, Central Aceh, Aceh. Issue 1 (November 2021) - Aprilla, R M; Artelin, N; Muklis, M; Miswar, E; Chaliluddin, M A; Agustina, I; Melanie, K
Abstract: Laut Tawar Lake is located in the town of Takengon, Central Aceh district. Currently, Laut Tawar Lake has been utilized by the surrounding community as a fishing spot. One of the fishing gears used by fishermen is Bubu wau . One of the catches obtained by fishermen is crayfish. The crayfish has a high economic value, so the lack of control over the intensity of the catch also causes the average size of the crayfish caught, because catching crayfish is a transition from catching Rasbora tawarensis . One of the problems that frequently occur and research on crayfish has never been done before. Therefore, this research needs to be done. The purpose of this study was to determine fishing catch compositions of Bubu wau and the size distribution of crayfish carapace length of Bubu Wau fishermen in the Teluk One-one, Laut Tawar Lake. The research was carried out in about March 2021. The description of the fishing catch composition was analyzed by using the describded method. The size distribution of crayfish carapace length was analyzed by the Sturgess rule. From the results of the study, it can be concluded that the catch compositions of Bubu wau in Teluk One-one are crayfish, suckermouth catfish, channeled apple snail and tilapia. The type of crayfish caught by fishermen's Bubu wau was Cherax quadricarinatus amount of 4232 individuals (89% of the total catch), where the total length of the dominant crayfish carapace was 4.4-4.9 cm with a total number of 1403 and the least with a size of 8.6-9.1 cm was 1 crayfish from the total catch